Malaysian institutional repositories approach on the preservation of their digital contents / Imilia Ibrahim, Azman Mat Isa and Zam Hariro Samsudin - Ibrahim, Imilia; Mat Isa, Azman; Samsudin, Zam Hariro (Faculty of Information Management, 2022)
The primary goal of institutional repository development is to increase the visibility of universities' knowledge output. Because of the complexity and rapid development of the digital environment, the sustainability of institu-tional repositories' collections may be jeopardised as they store and manage knowledge output created in digital forms. The purpose of this research is to look into how Malaysian institutional repositories preserve their digital content. Furthermore, the study would investigate the impediments to institu-tional repositories' implementation of digital preservation activities. This study used qualitative methods to gain a comprehensive understanding of how institutional repositories plan and manage their digital collections, as well as their operational and technical approaches. The study is hoped to contribute to better administration and sustainability of digital collections in Malaysian institutional repositories, as well as serve as a model for other in-stitutions involved in managing digital collections in the country.